Sociodemographic and health-related determinants for making repeated calls to a medical helpline: a prospective cohort study - Helle Collatz Christensen; Tom Møller; Mitti Blakoe; Hejdi Gamst-Jensen; My von Euler-Chelpin (BMJ Open)
Objectives To identify sociodemographic and health-related characteristics of callers’ making repeated calls within 48 hours to a medical helpline, compared with those who only call once.Setting In the Capital Region of Denmark people with acute, non-life-threatening illnesses or injuries are triaged through a single-tier medical helpline for acute, healthcare services.Participants People who called the medical helpline between 18 January and 9 February 2017 were invited to participate in the survey. During the period, 38 787 calls were handled and 12 902 agreed to participate. Calls were excluded because of the temporary civil registration number (n=78), the call was not made by the patient or a close relative (n=699), or survey responses were incomplete (n=19). Hence, the analysis included 12 106 calls, representing 11.131 callers’ making single calls and 464 callers’ making two or more calls within 48 hours. Callers’ data (age, sex and caller identification) were collected from the medical helpline’s electronic records. Data were enriched using the callers’ self-rated health, self-evaluated degree of worry, and registry data on income, ethnicity and comorbidities. The OR for making repeated calls was calculated in a crude, sex-adjusted and age-adjusted analysis and in a mutually adjusted analysis.Results The crude logistic regression analysis showed that age, self-rated health, self-evaluated degree of worry, income, ethnicity and comorbidities were significantly associated with making repeated calls. In the mutually adjusted analysis associations decreased, however, odds ratios remained significantly decreased for callers with a household income in the middle (OR=0.71;95% CI 0.54 to 0.92) or highest (OR=0.68;95% CI 0.48 to 0.96) quartiles, whereas immigrants had borderline significantly increased OR (OR=1.34;95% CI 0.96 to 1.86) for making repeated calls.Conclusions Findings suggest that income and ethnicity are potential determinants of callers’ need to make additional calls within 48 hours to a medical helpline with triage function.